Pengaruh Pembelajaran Kontekstual Pesisir Terhadap Kemampuan Komunikasi Matematis dan Disposisi Matematis Siswa SMP - Ahmad Rustam (Universitas Mathla'ul Anwar Banten, 2015)
The mathematical communication skill of SMP student is commonly still low. The problem is caused by lack of learning which relates mathematical material in the school with contextual problem especially at coastal context. Therefore, the need for learning that can sensitize the students in communicating the coastal problems in their environment. This is done to prevent the hands of irresponsible due to limited knowledge in developing coastal resources there. The aim of this research is to improve mathematical communication skill and disposition of student through the application of coastal contextual learning. Based on the analysis results, it can be concluded that overall mathematical communication skill and disposition of students which get coastal contextual learning have higher significant improvement than students who get PKV. The improvement of student mathematical communication skill which get coastal contextual learning is in moderate category, mean while mathematical disposition of student is in low one. Based on the analysis of interview and observation data show that coastal contextual learning can improve student’s activity in learning.